Efficient isolation of membrane-associated exopolysaccharides of four commercial bifidobacterial strains. (15th February 2022) - Ferrari, Michela; Hameleers, Lisanne; Stuart, Marc C.A.; Oerlemans, Marjolein M.P.; de Vos, Paul; Jurak, Edita; Walvoort, Marthe T.C.
Abstract: Bifidobacteria confer many health effects, such as fiber digestion, pathogen inhibition and immune system maturation, especially in the newborn infant. The bifidobacterial exopolysaccharides (EPS) are often associated with important health effects, but their thorough investigation is hampered by lack of knowledge of the EPS localization, which is important for efficient EPS isolation. Here we present a straightforward isolation procedure to obtain EPS of four commercial bifidobacterial strains ( B. adolescentis, B. bifidum, B. breve, and B. infantis ), that are localized at the cell membrane (evidenced using cryo-EM). This procedure can be applied to other bifidobacterial strains, to facilitate the easy isolation and purification for biological experiments and future application in nutraceuticals. In addition, we demonstrate structural differences in the EPS of the four bifidobacterial strains, in terms of monosaccharide composition and size, highlighting the potential of the isolated EPS for determining specific structure-activity effects of bifidobacteria. Graphical abstract: Unlabelled Image Highlights: Bifidobacterium adolescentis, B. bifidum, B. breve, and B. infantis have membrane-associated exopolysaccharides. The exopolysaccharides have distinct structural differences. Alkaline treatment efficiently releases the bifidobacterial EPS. MRS4 medium sustains growth and minimal purification steps are required to obtain pure EPS samples.